Statistics of the Audit Market in China - Ya. Liu (Учёт. Анализ. Аудит, 2024)
As the world’s second-largest economy, China has seen an increase in demand for auditing services in recent years. Auditing plays the role of “economic police” and is of great significance to the healthy and orderly development of the market economy. This study does not only enrich the theoretical study of China’s audit market, but also offers suggestions for its improvement, which have practical significance for the sustainable development of China’s audit market. The purpose of this study is to examine the situation on audit market in China, analyze its scale as well as the dynamics of audit in listed companies. As a methodological basis, the author used the works of the Russian scientist E. M. Gutzeit and reports on the audit market of the Ministry of Finance of the Russian Federation. The study reveals that the audit market in China is characterized by intense growth and concentration of large and medium-sized audit organizations; it is still dominated by traditional audit services; audit fees for listed companies are positively correlated with the size of the latter’s assets. The market leaders are the Big Four — Pricewaterhouse Coopers, Deloitte & Touche, Ernst & Young and KPMG. This study gives recommendations to the Ministry of Finance of China and the Chinese Institute of Certified Public Accountants: it is necessary to improve the system of state regulation of the audit market and encourage the establishment of self-regulation mechanisms; to actively expand the scope of audit organizations; to strengthen the branding of domestic audit companies.